Analisis Penerapan Biaya Lingkungan Dalam Kaitan Pelaporan Akuntansi Pada PLTMG 30 MW Baubau - Wahyuni, Diny; Abdullah, Muntu; Asni, Nur (Universitas 17 Agustus 1945 Jakarta, 2025)
This study aims to analyze the implementation of environmental cost accounting at the 30 MW Baubau Gas Engine Power Plant (PLTMG) through an assessment of five main stages: identification, recognition, measurement, presentation, and disclosure of environmental costs. This study employs a descriptive qualitative approach, encompassing primary and secondary data obtained through interviews, observations, and documentation. The results indicate that the implementation of environmental cost accounting at the 30 MW Baubau PLTMG reflects the company's commitment to sustainable environmental management. Environmental costs have been identified through a dedicated account named